EVALUATION OF THE LEVEL OF COMMUNITY KNOWLEDGE ABOUT HOW TO USE AND ANTIBIOTIC RESISTANCE IN DUPOK VILLAGE, BANGKALAN REGENCY - Rizal Umar; Riyadatus Solihah; Mufarika - (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Antibiotics are drugs that we often encounter in everyday life, not infrequently doctors often prescribe this one drug, but in use in the community there are still often errors in consuming antibiotics resulting in antibiotic resistance or resistance to an antibiotic. The occurrence of misuse of antibiotics is caused by lack of public knowledge and lack of education from medical personnel in hospitals. Low level of knowledge about the use of antibiotics can cause inappropriate use of antibiotics, so there is a risk of causing antibiotic side effects. Providing education is one way that can be used to increase knowledge about the rational use of antibiotics. The purpose of this study is to determine the level of public knowledge about how to use antibiotics and antibiotic resistance. The study was conducted in Dupok Village, Bangakalan Regency, this type of research was cross sectional through a survey with questionnaire media. Sampling was carried out using the cluster sampling method involving 100 households (Family Heads). The research instrument used was a closed questionnaire with a total of 10 questions. The data obtained is then analyzed descriptively.